张爱玲小说的批评体系研究: A Study on the Critical System of Zhang Ailing’s Novels - Ji Zhongxuan; Foo, Ai Peng (ERUDITE: Journal of Chinese Studies and Education, 2022)
张爱玲是中国现当代文坛上一位非常有特色的女作家，她透过作品中人物形象的生存轨迹为我们展现出了一个西方现代文明和东方没落文化结合后的畸形社会风貌，具有独特的文化内涵。学术界对张爱玲文章的研究开始于上个世纪四十年代，本文以年代为主线，梳理了张爱玲在中西方不同的时代背景与文化氛围中的研究概况，通过对张爱玲研究成果的梳理，我们可以看到特定的历史背景下，中西方不同的学术研究氛围与文学研究理念，所表现的不同视野和思路。Zhang Ailing is a very distinctive female writer in the modern and contemporary Chinese literary world. Through the survival track of the characters in her works, she shows us a deformed social style after the combination of Western modern civilization and Eastern declining culture, with unique cultural connotation. The academic circle began to study Eileen Zhang’s articles in the 1940s. This article uses time as the main line and sorted out the research overview of Eileen Zhang in different historical backgrounds and cultural atmospheres in China and the West. Through the combing of Eileen Zhang's research results, we can see that under a specific historical background, different academic research atmospheres and literary research concepts in China and the West have different perspectives and thoughts on the research of Eileen Chang’s articles.Keywords:  Zhang Ailing, Novel, Criticism system